Multiple pathways to the student brain : energizing and enhancing instruction - Zadina, Janet N. (San Francisco, CA : Jossey-Bass, 2014)
'From an award-winning neuroscience researcher with twenty years of teaching experience, Multiple Pathways to the Student Brain uses educator-friendly language to explain how the brain learns. Steering clear of'neuro-myths,' Dr. Janet Zadina discusses multiple brain pathways for learning and provides practical advice for creating a brain-compatible classroom. While there are an abundance of books and workshops that aim to integrate education and brain science, educators are seldom given concrete, actionable advice that makes a difference in the classroom. Multiple Pathways to the Student Brain bridges that divide by providing examples of strategies for day-to-day instruction aligned with the latest brain science. The book explains not only the sensory/motor pathways that are familiar to most educators (visual, auditory, and kinesthetic), it also explores the lesser known pathways--reward/survival, language, social, emotional, frontal lobe, and memory/attention--and how they can be tapped to energize and enhance instruction. Educators are forever searching for new and improved ways to convey information and inspire curiosity, and research suggests that exploiting different pathways may have a major effect on learning. Multiple Pathways to the Student Brain allows readers to see brain science through the eyes of a teacher--and teaching through the eyes of a brain scientist'--
Machine generated contents note: Acknowledgments Preface Introduction 1 How the Brain Thinks and Learns 2 The Sensory Motor Pathway 3 The Emotion Pathway 4 The Reward Pathway 5 The Attention and Memory Pathways 6 The Language and Math Pathways 7 The Frontal Lobe Executive Function Pathway 8 The Social Pathway 9 The Big Picture Bibliography The Author Index .
Includes bibliographical references and index.
Keywords: Learning, Psychology of; Learning -- Physiological aspects; Cognitive neuroscience